Desenvolvimento de um sistema para identificação de impactos de alta energia em aeronaves de asas rotativas proveniente de arma de fogo - Vinícius Samuel Pereira Silva (2020)
Consolidated as a versatile and indispensable instrument in the fight against crime, in the increase of security detection and in the support of different policing threats, the helicopter has proven its value due to its flight, to restrictions of use if it becomes necessary to maximize its employment to carry out perpetrate in the face of society's aggressor. The present work aimed to evaluate the feasibility of developing an avionic system capable of identifying high energy impacts from firearms on rotary wing aircraft. More specifically, it is essential to analyze the structural integrity of Aircraft Cell and GMP; Evaluate the specific vibration sources of the Eurocopter AS350B2 Helicopter according to engine and cell manufacturer maintenance manuals; Identify the vibrations present in the aircraft; monitor the vibrations captured in the aircraft in different flight modalities; Develop a vibration test bench capable of simulating and distinguishing vibrations originating from the aircraft from those caused by high energy impact; Simulate, identify and analyze high energy impacts on the aircraft using the Impact Hammer Test technique on the vibrational test bench; Identify, analyze and differentiate the high energy impacts from different firearms and their respective gauges on the elaborate vibrational test bench; Promote the overlapping of the “Damage Index” (vibrational interference produced in the system) over the aircraft's “Baseline” through Matlab software. To this end, the methodology was divided into five steps. In the first stage, reviews of the works on the subject were described. In the second, the previous GMP and cell inspections were detailed on the aircraft studied, in the third the engine vibration analysis parameters were detailed accompanied by the main rotor specific inspections, from the GMP drive shaft to the rear gearbox (CTT) and the tail rotor. Finally, an engine study test and Engineer Power Check (PWC) flight. In the fourth stage, the intended techniques of identification, processing and analysis of high energy mechanical shocks (SHM) in the aircraft, their laboratory simulations and the vibration identification procedures of AS350 B2 aircraft were specified. And finally, in the last one, the simulations of high energy shocks from firearms in the aircraft were detailed. The results indicate the feasibility for the development of a continuous vibration detection system in helicopters, which due to its attributions promote flights in diverse environments, susceptible to being hit by high energy mechanical shocks, birds, objects thrown on them, or even shots. of high-energy firearms on aircraft used by Brazilian police forces, devoid of this monitoring technology.